STUDI DESKRIPTIF TENTANG KEGIATAN MENARI PADA ANAK USIA DINI DI TK AN-NUR DESA SIMPANG TIGA KECAMATAN HAMPARAN RAWANG KOTA SUNGAI PENUH - Huljannah, Annisa; Iriani, Zora; Asriati, Afifah (SENDRATASIK UNP, 2019)
Abstract This study aims to determine and describe a descriptive study of the dancing activity at the Kindergarten An-Nur Simpang Tiga, Hamparan Rawang District, Sungai Penuh City. This type of research was qualitative research with a descriptive analysis approach. The instruments in this study were the researchers themselves and assisted with supporting instruments such as stationery and cameras. Then, the type of research used primary data and secondary data. Data collection techniques were carried out by means of library studies, observations (observations), interviews and documentation. Next, the steps in analyzing the data were data reduction, data presentation, verification and conclusions. The results showed that there were two dancing activities namely learning activities program and non learning program at An-Nur Kindergarten, Simpang Tiga, Hamparan Rawang District, Sungai Penuh. The dances are taught namely animal dance as the learning activity program and the Depati Parbo dance taught as the non leraning program. The planning carries out before the dance learning program by making RPPM and RPPH. Whereas, the planning for non learning program is arranged to make a special schedule for training the children to participate in dancing and prepare everything what the children need when practicing and performing the dance. Keywords: descriptive study, dancing activities, early childhood.